The offshore protection of Malaysian leatherback turtles - Chan, E. H.; Liew, Hee Chong (1989)
The imminent extinction of the leatherback turtle in Malaysia looms over our heads.The number of turtles visiting our beaches continue to decline. Concerted effort is being undertaken by the concerned local authorities to protect the turtles at their nesting beaches. The sale and consumption of leatherback eggs has been banned by law in Terengganu and all eggs deposited on the beaches are replanted in protected government beach hatcheries. However, grotection of leatherback turtles should not be confined to the time when they land on the beaches to nest. Offshore protection during the nesting season should take equal. if not top priority in the conservation of leatherback turtles. During the nesting season from May to September, an individual female turtle may reside in inshore national waters for periods approaching three months. During this time, incidental captures in fishing gear pOse a serious threat to the survival of the turtles at sea. In an effort to translate the concept of offshore protection into reality, Universiti Pertanian Malays'ia, in collaboration with the University of Georgia, has identified the internesting habitats of the leatherback turtles in Terengganu, using radio telemetry. The boundaries of a proposed restricted fishing zone is discussed in relation to the newly acquired information on the offshore and longshore ranges off the leatherbacks during the internesting period. Other approaches to offshore protection are also presented. Incidental captures in international waters and their effects on the Malays ian leatherback population are highl ighted. The vulnerability of hatchlings in the open sea is discussed as well.